Supported transition metal phosphide catalysts and methods for their preparation

CN118356954BActive Publication Date: 2026-10-30SHANGHAI SHAANXI COAL HIGH-TECH RES INST CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410466867.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-18
Publication Date
2026-10-30
Estimated Expiration
2044-04-18

AI Technical Summary

Technical Problem

然而其CO2转化度仍然处于较低水平,难以真正应用于工业化生产

Benefits of technology

[0019](1)本发明所述的负载型过渡金属磷化物催化剂在引入P后,过渡金属M被夺取了部分自由电子,偏向氧化态,并且P会与M结合形成M2P。磷化程度较低时,催化剂中会同时存在M与M2P,形成异质结(M-M2P)。当金属M与P的摩尔比为1:1(M:P=1:1)时,催化剂中的过渡金属M完全转变为M2P。使得负载型过渡金属磷化物催化剂仅需牺牲小部分催化活性的同时就能将主要产物由CH4转变为CO,大幅度提升了CO选择性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118356954B_ABST
    Figure CN118356954B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of supported transition metal phosphide catalyst and its preparation method, belong to catalyst technical field.The preparation method of the present application includes the following steps: carrier and phosphorus source solution are sequentially added to transition metal source solution, heated by stirring, drying, heat treatment, and the supported transition metal phosphide catalyst of the present application is obtained;Transition metal source solution is obtained by dissolving the chloride or nitrate of transition metal in first solvent;Phosphorus source solution is obtained by dissolving phosphorus source in second solvent.The catalyst of the present application changes the crystal lattice of metal Ru by the introduction of P, and then changes into Ru2P, and P doping effectively improves the dispersity and anti-sintering capacity of metal catalyst, and then significantly promotes the CO2 hydrogenation product selectivity from CH4 to CO change.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalyst technology, and particularly relates to a supported transition metal phosphide catalyst and its preparation method. Background Technology

[0002] Catalysis technology is a cornerstone of modern human production and life, but it also presents a significant problem of high energy consumption. For example, the process of synthetic ammonia alone consumes 1.3% of the global energy supply annually, while accounting for approximately 2% of global CO2 emissions. Developing economical and environmentally friendly catalytic processes is an ongoing goal, requiring the continuous development of catalysts with higher activity, tunable selectivity, and superior stability. For most industrial catalytic processes, transition metal-based catalysts remain the most popular on the market. To this end, researchers have been dedicated to precisely tuning the electronic structure and surface geometry of transition metals to optimize catalytic performance, such as through alloying, particle size or morphology adjustment, and metal-support interaction modification.

[0003] In existing technologies, nickel phosphide (Ni) 12 P5 is used in reverse water gas reaction, but its catalytic activity is not high, the conversion of CO2 in the reaction gas is not ideal, and it is difficult to industrialize.

[0004] Adding light elements (H, B, C, N, P, etc.) to TM catalysts can effectively alter the electronic and geometric structures of active sites, thereby improving catalytic performance. CO2 hydrogenation is a key method for converting CO2 and H2 into valuable chemicals, offering great promise for large-scale CO2 conversion and chemical production. The addition of phosphorus (P) to catalysts has been widely demonstrated to significantly alter the product selectivity from CH4 to CO during CO2 hydrogenation. This change is generally attributed to P-induced electronic or geometric effects, leading to alterations in the adsorption strength of CO by the active metal. Xu Yangfan et al. also observed that the introduction of P enhanced the length of Ni-Ni bonds, reducing bridging CO adsorbate species and improving CO selectivity during photothermal CO2 hydrogenation. However, the CO2 conversion rate remains relatively low, making it difficult to truly apply to industrial production. Therefore, constructing an RWGS catalyst with high CO2 conversion and high CO selectivity is both challenging and essential. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention provides a supported transition metal phosphide catalyst and its preparation method.

[0006] The first objective of this invention is to provide a method for preparing a supported transition metal phosphide catalyst, comprising the following steps: sequentially adding a support and a phosphorus source solution to a transition metal source solution, followed by stirring, heating, drying, and heat treatment to obtain the supported transition metal phosphide catalyst;

[0007] The transition metal source solution is obtained by dissolving the chloride or nitrate of the transition metal in a first solvent;

[0008] The phosphorus source solution is obtained by dissolving a phosphorus source in a second solvent.

[0009] In one embodiment of the present invention, the transition metal is selected from nickel, cobalt, iron or ruthenium.

[0010] In one embodiment of the present invention, the carrier is selected from silicon dioxide and / or titanium dioxide.

[0011] In one embodiment of the present invention, the phosphorus source is selected from sodium hypophosphite and / or sodium hypophosphite.

[0012] In one embodiment of the present invention, the stirring and heating speed is 35 r / min-45 r / min, the time is 55 min-65 min, and the temperature is 75℃-85℃.

[0013] In one embodiment of the present invention, the heat treatment is a reduction at 550°C-650°C for 250-350 minutes in a hydrogen atmosphere.

[0014] In one embodiment of the present invention, the flow rate of the hydrogen gas is 45 mL / min to 55 mL / min.

[0015] In one embodiment of the present invention, the concentration of the transition metal source solution is 0.8 mg / mL-1.2 mg / mL; the concentration of the phosphorus source solution is 0.8 mg / mL-1.2 mg / mL; and the volume ratio of the transition metal source solution to the phosphorus source solution is 77:4-40.

[0016] In one embodiment of the present invention, both the first solvent and the second solvent are ethanol.

[0017] A second objective of this invention is to provide a supported transition metal phosphide catalyst prepared by the method described above.

[0018] The technical solution of the present invention has the following advantages compared with the prior art:

[0019] (1) In the supported transition metal phosphide catalyst of the present invention, after the introduction of P, the transition metal M loses some free electrons and becomes biased towards the oxidation state, and P combines with M to form M2P. When the degree of phosphating is low, M and M2P coexist in the catalyst, forming a heterojunction (M-M2P). When the molar ratio of metal M to P is 1:1 (M:P = 1:1), the transition metal M in the catalyst is completely converted into M2P. This allows the supported transition metal phosphide catalyst to convert the main product from CH4 to CO with only a small amount of catalytic activity, significantly improving CO selectivity.

[0020] (2) The synthesis method of the supported transition metal phosphide catalyst described in this invention is simple and has excellent catalytic performance. The catalytic performance of the catalyst depends on the nature of the active site. By introducing P, the lattice of metal Ru is changed, and then Ru2P is transformed. Furthermore, P doping effectively improves the dispersion and anti-sintering ability of the metal catalyst, thereby significantly promoting the selective transformation of CO2 hydrogenation products from CH4 to CO. Attached Figure Description

[0021] To make the content of this invention easier to understand, the invention will be further described in detail below with reference to specific embodiments and accompanying drawings, wherein:

[0022] Figure 1 This is a flowchart illustrating the preparation route of RuP / SiO2 catalysts with different ruthenium-phosphorus ratios in Example 1 of the present invention.

[0023] Figure 2 This is a flowchart illustrating the preparation route of the Ru / SiO2 catalyst in Comparative Example 1 of the present invention.

[0024] Figure 3 The image shows the characterization of Test Example 1 of the present invention; where ad are TEM images of Ru / SiO2, RuP(5:1), RuP(10:1) and RuP(1:1) catalysts, respectively, and e is a high-resolution TEM image and a selected area electron diffraction (SAED) image of the RuP(5:1) catalyst.

[0025] Figure 4 This is a particle size distribution diagram of Test Example 1 of the present invention; where ad represents RuP (1:1), RuP (5:1), RuP (10:1) and Ru / SiO2, respectively.

[0026] Figure 5 This is the XPS spectrum of test example 2 of the present invention; where a is Ru 3p and b is P 2p;

[0027] Figure 6The diagram shows the chemical structure and coordination environment of test example 3 of the present invention; where a is the Ru K-side XANES spectrum, b is the EXAFS spectrum, and c is the DRIFT spectrum of adsorbed CO. Detailed Implementation

[0028] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. It should be understood that the specific embodiments are only used to explain the present invention, but the embodiments are not intended to limit the present invention.

[0029] In this invention, unless otherwise stated, the technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0030] In this invention, unless otherwise stated, the term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0031] In this invention, unless otherwise specified, the experimental methods used in the embodiments of this invention are conventional methods, and the materials and reagents used are commercially available unless otherwise specified.

[0032] Example 1

[0033] Reference Figure 1 As shown, the RuP / SiO2 catalysts with different ruthenium-phosphorus ratios and their preparation methods in this embodiment specifically include the following steps:

[0034] S1. First, weigh 50 mg of RuCl3 and 50 mg of NaH2PO2 using an electronic analytical balance, dissolve them in 50 mL of anhydrous ethanol, and sonicate them in an ultrasonic cleaner for 60 min to disperse RuCl3 and NaH2PO2·H2O evenly, so as to obtain RuCl3 solution and NaH2PO2·H2O solution with concentrations of 1 mg / mL, respectively.

[0035] S2. Then, use a pipette to measure 30.8 mL of RuCl3 solution and add it dropwise to a 100 mL beaker; then use an electronic analytical balance to weigh 300 mg of 80-mesh high specific surface area SiO2 support and add it to the beaker containing RuCl3 solution; then use a pipette to measure 1.6 mL, 3.2 mL and 15.8 mL of NaH2PO2·H2O solution into the beakers respectively, place them on a magnetic stirrer and stir at 40 r / min for 60 min. After stirring evenly, heat and stir at 80℃ and 40 r / min until dried into powder;

[0036] S3. Finally, the obtained powder was reduced for 300 min in a hydrogen atmosphere at 50 mL / min and at 600 °C. According to the Ru:P molar ratio, the RuP / SiO2 catalysts were named RuP(10:1), RuP(5:1) and RuP(1:1), respectively.

[0037] Comparative Example 1

[0038] Reference Figure 2 As shown, the preparation of the Ru / SiO2 catalyst in this comparative example is basically the same as in Example 1, except that NaH2PO2·H2O is not added. Specifically, it includes the following steps:

[0039] S1. First, weigh 50 mg of RuCl3 using an electronic analytical balance, dissolve it in 50 mL of anhydrous ethanol, and sonicate it in an ultrasonic cleaner for 60 min to disperse RuCl3 evenly, thus obtaining a RuCl3 solution with a concentration of 1 mg / mL.

[0040] S2. Then, use a pipette to measure 30.8 mL of RuCl3 solution and add it dropwise into a 100 mL beaker; then use an electronic analytical balance to weigh 300 mg of 80-mesh high specific surface area SiO2 support and add it to the beaker of RuCl3 solution. Place it on a magnetic stirrer and stir at 40 r / min for 60 min. After stirring evenly, heat and stir at 80℃ and 40 r / min until it is dried into powder.

[0041] S3. Finally, the obtained powder was reduced for 300 min in a hydrogen atmosphere at 50 mL / min and 600 °C to obtain a 5 wt% Ru / SiO2 catalyst, which is called Ru / SiO2.

[0042] Test Example 1

[0043] Based on Example 1 and Comparative Example 1, the prepared RuP(10:1), RuP(5:1), RuP(1:1), and Ru / SiO2 were characterized, and the results are as follows: Figure 3-4 As shown. From Figure 3 a and Figure 4 As can be seen from d, high-resolution transmission electron microscopy (TEM) imaging of the hydrogen-reduced Ru / SiO2 catalyst reveals that the reduced metallic Ru aggregates into unevenly sized particles on the SiO2 support surface, with an average particle size of ~7.7±0.8 nm. Figure 3 b-3d and Figure 4As shown in a-4c, with the introduction of P, the dispersion of Ru metal particles on the surface of RuP(10:1), RuP(5:1), and RuP(1:1) catalysts changed significantly, transforming from unevenly sized Ru / SiO2 metal particles to uniformly dispersed small particles. Furthermore, the higher the degree of phosphating, the more uniform the metal particle distribution and the smaller the average particle size. After the introduction of P, the metal particle size on the surface of RuP(1:1), RuP(5:1), and RuP(10:1) catalysts changed from ~7.7±0.8 nm in Ru / SiO2 to ~2.2±0.6 nm, ~3.0±0.8 nm, and ~3.1±0.7 nm, respectively. This demonstrates that the introduction of P can effectively reduce the sintering and agglomeration of metallic Ru, improve particle dispersion, and reduce particle size. All four samples were obtained by sintering at 600℃ for 5 hours, which preliminarily verifies that RuP(10:1), RuP(5:1) and RuP(1:1) catalysts have excellent anti-sintering properties and high-temperature stability.

[0044] Furthermore, although the introduction of a small amount of P did not lead to the appearance of Ru2P diffraction peaks, Ru2P species were observed in high-resolution TEM images. Figure 3 As can be seen, lattice fringes corresponding to the Ru(101) and Ru2P(112) planes were observed in the same nanoparticle on RuP(5:1), indicating that the introduction of a small amount of P induces the formation of a Ru-Ru2P heterojunction. That is, the introduction of P preferentially forms Ru2P with Ru. However, when the amount of P is insufficient to completely phosphorylate the Ru nanoparticles, it will partially phosphorylate the Ru nanoparticles, thereby forming a Ru-Ru2P heterojunction. The P in the heterojunction acts as a "barrier," hindering hydrogen overflow on the catalyst surface, suppressing subsequent CO hydrogenation, and thus preventing CH4 formation.

[0045] Test Example 2

[0046] Based on Example 1 and Comparative Example 1, XPS tests were performed on the prepared RuP(10:1), RuP(5:1), RuP(1:1), and Ru / SiO2, and the results are as follows. Figure 5 As shown. From Figure 5 As can be seen, the XPS peaks at 461eV-462eV and 483eV-485.0eV belong to the metal Ru. 4+ The XPS peaks at 463.9 eV and 486.7 eV are attributed to RuO3p3 / 2 and 3p1 / 2, respectively. The RuO3 / 3p3 / 2 and 3p1 / 2 peaks in the Ru / SiO2 catalyst are associated with RuO3p3 / 2 and 3p1 / 2. 4+ The peaks at 3p3 / 2 and 3p1 / 2 are 641.4 eV and 483.5 eV, respectively. After the introduction of P, the RuP(10:1), RuP(5:1), and RuP(1:1) catalysts exhibit [various effects]. 4+The 3p3 / 2 peak shifted to 461.6 eV, 461.8 eV, and 461.9 eV, Ru 4+ The 3p³ / 2 peak shifted to 483.7 eV, 484.3 eV, and 484.4 eV. The peak areas of the PC and PO peaks of the 2p P orbitals in the catalyst are related to the P content in the catalyst. In the three catalysts RuP (10:1), RuP (5:1), and RuP (1:1), the peak areas of the corresponding PC and PO peaks of the P 2p orbitals also increase with the increase of P content. Figure 5 (b) Correspondingly, the valence state of Ru metal gradually increases. TEM analysis revealed that P captures some free electrons from Ru, resulting in Ru₂P in the catalyst. When the phosphating degree is insufficient, some Ru₂P coexists with Ru, forming a heterojunction. Compared to the Ru / SiO₂ catalyst, the RuP catalyst significantly improves CO selectivity by converting the main product from CH₄ to CO while sacrificing a small portion of catalytic activity.

[0047] Test Example 3

[0048] Based on Example 1 and Comparative Example 1, the chemical structures and coordination environments of RuP(10:1), RuP(5:1), RuP(1:1), and Ru / SiO2 were investigated, and the results are as follows: Figure 6 As shown. From Figure 6 It can be seen that with the introduction of P, the Ru K-edge shifts to higher energies, which means that Ru species are in an oxidized state. These results indicate that as the proportion of Ru₂P in nanoparticles increases, more P accepts electrons from Ru, and more Ru species exhibit an electron-deficient state (Ru₂P). δ+ ()( Figure 6 a). Furthermore, the RuK edge-extended X-ray absorption fine structure (EXAFS) results indicate that metallic Ru-Ru coordination is the dominant coordination structure of Ru atoms in Ru / SiO2, RuP(10:1), and RuP(5:1), while Ru in RuP(1:1) / SiO2 is mainly coordinated by Ru-P of Ru2P. Figure 6 b), which is consistent with the XRD results. Meanwhile, Ru-P coordination of Ru2P was also observed in RuP(10:1) and RuP(5:1), indicating that Ru2P coexists with Ru in the catalyst, further confirming the Ru / Ru2P heterojunction structure.

[0049] Furthermore, the P atoms coordinated with Ru can accept electrons from Ru atoms, and electron transfer between Ru and Ru₂P should also occur in the Ru / Ru₂P heterostructure. To demonstrate this hypothesis, DRIFTTS spectra of Ru / SiO₂, RuP(10:1), RuP(5:1), and RuP(1:1) catalysts after CO adsorption were collected. Figure 6As shown in c, the Ru / SiO2 catalyst at 2133 cm⁻¹ -1 2070cm -1 and 2010cm -1 Four distinct CO adsorption peaks appeared at 1962 cm⁻¹, corresponding to linear CO adsorption and bridged CO adsorption, respectively. -1 In Ru / SiO2, RuP(10:1), and RuP(5:1) catalysts, only ~2010 cm⁻¹ -1 The peak at [value] underwent a blue shift with the introduction of P, while the positions of other peaks remained unchanged. For the RuP(1:1) catalyst, the intensity of the CO adsorption peak decreased significantly, reaching only 2067 cm⁻¹. -1 Linear CO adsorption peak and bridging adsorption peak at 2002 cm⁻¹ -1 These results indicate that Ru2P in the heterojunction structure can accept electrons from Ru, thereby weakening the adsorption of CO by Ru sites. While CO can also be adsorbed on Ru2P, its adsorption capacity is weaker compared to that of metallic Ru sites.

[0050] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A method for preparing a supported transition metal phosphide catalyst, characterized in that, Includes the following steps: The supported transition metal phosphide catalyst was obtained by sequentially adding a support and a phosphorus source solution to a transition metal source solution, followed by stirring, heating, drying, and reduction heat treatment under a hydrogen atmosphere. The transition metal source solution is obtained by dissolving the chloride or nitrate of the transition metal in a first solvent; the transition metal is selected from ruthenium, and the catalyst contains a Ru-Ru2P heterojunction; The phosphorus source solution is obtained by dissolving a phosphorus source in a second solvent; the phosphorus source is selected from sodium hypophosphite and / or sodium hypophosphite. Both the first solvent and the second solvent are ethanol.

2. The method for preparing the supported transition metal phosphide catalyst according to claim 1, characterized in that, The carrier is selected from silicon dioxide and / or titanium dioxide.

3. The method for preparing the supported transition metal phosphide catalyst according to claim 1, characterized in that, The stirring and heating speed is 35 r / min-45 r / min, the time is 55 min-65 min, and the temperature is 75℃-85℃.

4. The method for preparing the supported transition metal phosphide catalyst according to claim 1, characterized in that, The heat treatment is performed under a hydrogen atmosphere, with a reduction temperature of 550℃-650℃ for 250-350 minutes.

5. The method for preparing the supported transition metal phosphide catalyst according to claim 1, characterized in that, The flow rate of the hydrogen gas is 45 mL / min to 55 mL / min.

6. The method for preparing the supported transition metal phosphide catalyst according to claim 1, characterized in that, The concentration of the transition metal source solution is 0.8 mg / mL to 1.2 mg / mL; the concentration of the phosphorus source solution is 0.8 mg / mL to 1.2 mg / mL; and the volume ratio of the transition metal source solution to the phosphorus source solution is 77:4-40.

7. A supported transition metal phosphide catalyst prepared by the method of any one of claims 1-6.